2010
DOI: 10.2174/156720510791162430
|View full text |Cite
|
Sign up to set email alerts
|

Cross Sectional Observational Study on the Societal Costs of Alzheimers Disease

Abstract: The societal costs of AD are very high, especially for patients with moderate and severe AD. This implies that treatments with the ability to delay progression of the disease into more severe stages have the potential to save large costs for society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
90
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(96 citation statements)
references
References 20 publications
4
90
1
1
Order By: Relevance
“…That way, the economic value of informal care is €2100 in mild and €2400 in moderate dementia covering around 50% respectively 33% of total costs. Other studies differentiated opportunity costs of lost leisure time and forgone working hours [43], assigned small flat-rate amounts [8] or relied on the caregivers' individual wage rate [42]. These approaches led altogether to more conservative cost estimates than ours.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…That way, the economic value of informal care is €2100 in mild and €2400 in moderate dementia covering around 50% respectively 33% of total costs. Other studies differentiated opportunity costs of lost leisure time and forgone working hours [43], assigned small flat-rate amounts [8] or relied on the caregivers' individual wage rate [42]. These approaches led altogether to more conservative cost estimates than ours.…”
Section: Discussionmentioning
confidence: 93%
“…Therefore all studies exclusively working with insurance claims data disregard the substantial impact of valued informal care in costs of dementia care. In this context, collecting information on care giving time of all informal caregivers is a further strength of our study that allows a more realistic estimation of societal costs than studies that only regard care giving time of the main caregiver (as example see [8,43]). Previous work on IDA data, suggests an underestimation of care giving time up to 10% if the support of additional caregivers is disregarded [27].…”
Section: Discussionmentioning
confidence: 99%
“…Available cost studies from several European countries show a strong positive relationship between disease severity and total costs of care [1,[3][4][5][6][7][8]. Informal care costs form the major component of societal costs for community-dwelling AD dementia patients [8][9][10][11], and the cost of institutional care is the other main cost driver in the long-term care of patients with AD dementia [12].…”
Section: Introductionmentioning
confidence: 99%
“…If the purpose is limited to analysis of costs in a pharmacoeconomic evaluation, the main criterion must be that the chosen vehicle has a strong correlation with costs, while in costeffectiveness analyses it is important that the outcome is clinically relevant 10 . As the basic design of the present study was a cost analysis, we used ADL as the vehicle of costs, as recent studies have shown that ADL is a better predictor of costs than cognitive function 22,42 . From a cost-consequences viewpoint, considering the results of the present cost analysis in the context of the available clinical data for galantamine [16][17][18][19][20][21] , there is indirect evidence for cost-effectiveness of galantamine.…”
Section: Discussionmentioning
confidence: 99%